Survival strategies: a New Zealand hospitality habitual entrepreneur - Neill, LJ; Liu, C (Bogazici University, 2011)
The purpose of this paper is to report the findings of case study research conducted in Auckland, New Zealand in 2010. This research examined the motivators prompting a habitual entrepreneur to engage within new venture start ups within the vibrant hospitality industry. This paper focuses on explaining how and why an entrepreneur within the highly competitive hospitality industry seeks business expansion via habitual entrepreneurship during economic recession. The research involves in-depth interviews of a successful hospitality habitual entrepreneur. This paper reports on the New Zealand entrepreneur’s personal and business profile, motivations that prompt entrepreneurship, business management strategies and the wider factors affecting his success. This study provides insights into the characteristics and behaviours of habitual entrepreneurs within a New Zealand hospitality context. Therefore, this paper contributes to entrepreneurship literature by demystifying New Zealand’s unique and innovative mindset the ‘number eight wire’ mentality.
Keywords: Hospitality entrepreneurship; Habitual entrepreneur; Entrepreneurial characteristics; New Zealand.